2003
DOI: 10.1046/j.1365-2745.2003.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil N dynamics in relation to leaf litter quality and soil fertility in north‐western Patagonian forests

Abstract: Summary 1We examined the relationships among soil N dynamics, soil chemistry and leaf litter quality in 28 forest stands dominated by conifers, woody broad-leaf deciduous species or broad-leaf evergreens. Potential net N mineralization, net nitrification and microbial biomass N were used as indicators of soil N dynamics; pH, organic C, total N, exchangeable cations and extractable P as indicators of soil chemistry and N concentration, lignin concentration, C : N ratio and lignin : N ratio in senescent leaves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
79
4
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 37 publications
13
79
4
1
Order By: Relevance
“…Comparing previous studies on soil fertility variables in post-fire Challhuaco Valley (Satti et al 2003, Alauzis et al 2004, Kitzberger et al 2005 with the results obtained in the present study, a lack of recovery in soil fertility eight years after fire (carbon, nitrogen, microbial nitrogen flush, pH, potassium and extractable phosphorus, for example) can be observed. This indicates the high disturbance intensity and the low post-disturbance resilience of these forests.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Comparing previous studies on soil fertility variables in post-fire Challhuaco Valley (Satti et al 2003, Alauzis et al 2004, Kitzberger et al 2005 with the results obtained in the present study, a lack of recovery in soil fertility eight years after fire (carbon, nitrogen, microbial nitrogen flush, pH, potassium and extractable phosphorus, for example) can be observed. This indicates the high disturbance intensity and the low post-disturbance resilience of these forests.…”
Section: Discussionsupporting
confidence: 87%
“…Alauzis et al (2004) found that four years after fire, burnt soils showed no recovery compared to soil in unburnt conditions. The main effects on organic carbon, total nitrogen, extractable phosphorus and microbial biomass were recorded by these and other authors (Diehl et al 2003, Satti et al 2003, Kitzberger et al 2005.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Soils of unpolluted, old-growth temperate forests in Chile and Argentina present a high ratio of net nitrification in relation to net mineralized N; either potential (Pérez et al, 1998;Satti et al, 2003) or in situ (Pérez et al, 1998;Decker and Boerner, 2003). However nitrate pools in forest soils and nitrate losses to stream waters are extremely low because of a high N retention in soil organic matter (Perakis and Hedin, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence shows that forest logging increases N availability through higher rates of mineralization (Reynolds et al, 2000;Thibodeau et al, 2000;Hope et al, 2003;Lindo and Visser, 2003;Inagaki et al, 2008) and decomposition (Prescott, 1997;Brais et al, 2002), leading to increased availability of labile C (Chatterjee et al, 2008) and higher denitrification (Robertson and Tiedje, 1988). However, the effects of altering the inputs of reactive N and land use change in N transformations are less understood in southern temperate forests, where N is strongly limiting for tree growth (Perakis and Hedin, 2001;Vann et al, 2002;Satti et al, 2003;Diehl et al, 2008), and soils are dominated by recalcitrant forms of C, as indicated by the relatively high soil C/N ratios (Pérez et al, 2009). Such analysis is relevant because one of the important microbial transformations in the context of global change is denitrification, as it may counteract eutrophication in aquatic ecosystems and also may be a significant source of N 2 O, an important greenhouse gas.…”
Section: Introductionmentioning
confidence: 99%